Studi Perbandingan Kinerja PLTD Gunung Belah pada Penggunaan Biodiesel B35 dan B40: Tinjauan Teknis dan Dampaknya terhadap Keandalan Operasional - Bobby Galang Samudra; M Raafi Aqil Firdaus; Rudy Laksmono; Sri Yanto (Universitas Al Azhar Indonesia, 2026)
In response to rising global energy uncertainty and geopolitical fragmentation, Indonesia has accelerated its energy transition through the development of high-percentage biodiesel blends. This study analyzes diesel engine performance using B35 (2024) and B40 (2025) blends to assess their technical feasibility and impact on national energy resilience. Using a quantitative experimental method, daily energy production data from three diesel generator (PLTD) units were collected over four months under real operating conditions. The 2024 results show that B35 produced a consistent increase in monthly output, peaking at more than 1,025 MWh in April, indicating good combustion efficiency and operational stability. In contrast, 2025 data show that B40 exhibited more fluctuating performance, with peak output in March but a decline in April due to system load prioritization. Nevertheless, B40 demonstrated potential for better thermal efficiency and specific fuel consumption (SFC) if load management is optimized. These findings highlight the need for adaptive system management and infrastructure readiness to support the integration of high-percentage biodiesel, thereby strengthening Indonesia’s energy transition and national energy independence.Keywords - Biodiesel B40; Diesel Engine Performance; Energy Security; SFC; Renewable Transition.